The State of the Art of the DSM-5 "with Mixed Features" Specifier. (25th August 2015) - Verdolini, Norma; Agius, Mark; Ferranti, Laura; Moretti, Patrizia; Piselli, Massimiliano; Quartesan, Roberto
Abstract : The new DSM-5 "with mixed features" specifier (MFS) has renewed the interest of the scientific community in mixed states, leading not only to new clinical studies but also to new criticisms of the current nosology. Consequently, in our paper we have reviewed the latest literature, trying to understand the reactions of psychiatrists to the new nosology and its epidemiological, prognostic, and clinical consequences. It seems that the most widespread major criticism is the exclusion from the DSM-5 MFS of overlapping symptoms (such as psychomotor agitation, irritability, and distractibility), with a consequent reduction in diagnostic power. On the other hand, undoubtedly the new DSM-5 classification has helped to identify more patients suffering from a mixed state by broadening the narrow DSM-IV-TR criteria. As for the clinical presentation, the epidemiological data, and the therapeutic outcomes, the latest literature does not point out a univocal point of view and further research is needed to fully assess the implications of the new DSM-5 MFS. It is our view that a diagnostic category should be preferred to a specifier and mixed states should be better considered as a spectrum of states, according to what was stated many years ago by Kraepelin.